2012
DOI: 10.3109/08037051.2012.656397
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of aortic elastic properties in patients with sarcoidosis

Abstract: We observed that elastic properties of the aorta alter in patients with sarcoidosis. We also have demonstrated a statistically significant correlation between aortic elastic properties and the disease duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…22 Sarcoidosis has been associated with an increased pulse wave index which may predict the early stages of atherosclerosis. 3,4,6,11…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Sarcoidosis has been associated with an increased pulse wave index which may predict the early stages of atherosclerosis. 3,4,6,11…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Some reports indicate increased arterial stiffness in sarcoidosis, reflecting a very early stage of atherosclerosis. 3,4 The most important mechanism underlying atherosclerotic vascular changes in sarcoidosis is chronic inflammation while it may also be due to increased oxidative stress and low high-density lipoprotein cholesterol (HDL-C) levels since all of these are proatherogenic. 5 7…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Kizer et al 10 previously suggested a possible link between fibrotic lung diseases and increased prevalence of CVD. Furthermore, Ardic et al 11 recently reported alteration in elastic properties of the aorta, and data from Ivanisevic et al 12 revealed elevated oxidative stress, diminished antioxidative protection, and altered lipid profile in patients with sarcoidosis. The latest data from a prospective study including various forms of immune-mediated disorders demonstrated that patients with sarcoidosis also have significantly increased risk of hospitalization due to coronary artery disease, similar to patients suffering from other systemic inflammatory diseases.…”
mentioning
confidence: 99%
“…Aortic distensibility was lower and aortic stiffness was higher in patients with cystic fibrosis compared with healthy controls, even before development of pulmonary hypertension. 14 Similar changes were observed in patients with subclinical hypothyroidism, 15 sarcoidosis, 16 α1-antitrypsin deficiency, 17 erectile dysfunction, 18 obstructive sleep apnea, 19 chronic kidney disease, 20 metabolic syndrome, 21 hypertrophic cardiomyopathy, 22 and coronary artery disease (Table 1). 23…”
Section: Resultsmentioning
confidence: 62%